1997
DOI: 10.1007/s004380050507
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two functional serine/threonine protein kinases from soyabean that have an unusual acidic domain at the carboxy terminus

Abstract: Two soybean cDNA clones, SPK-3 and SPK-4, encoding putative protein kinases were isolated and characterized. Both cDNAs encoded approximately 40-kDa serine/threonine kinases with unusual stretches of acidic amino acids in their carboxy-terminal regions, which are highly homologous to PKABA1 from wheat and ASKs from Arabidopsis. These kinases are encoded by one- or two-copy genes in the soybean genome. Notably, SPK-3 and -4 showed different patterns of expression in various soybean tissues. SPK-3 is highly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
(64 reference statements)
1
39
0
1
Order By: Relevance
“…SAC3 is a type 2 SNF1-related kinase (SnRK2) and is similar to family kinases found in vascular plants. Several of these SnRK2-encoding transcripts increase in abundance in response to environmental stresses (Anderberg and WalkerSimmons, 1992;Park et al, 1993;Yoon et al, 1997), but the function of most of the SnRK2 proteins found in plants have yet to be elucidated. Arabidopsis contains at least 12 SnRK2 proteins that have significant similarity (49% amino acid identity and 60% amino acid similarity over most of the protein) with SAC3.…”
Section: Regulation Of the Cys Biosynthetic Pathwaymentioning
confidence: 99%
“…SAC3 is a type 2 SNF1-related kinase (SnRK2) and is similar to family kinases found in vascular plants. Several of these SnRK2-encoding transcripts increase in abundance in response to environmental stresses (Anderberg and WalkerSimmons, 1992;Park et al, 1993;Yoon et al, 1997), but the function of most of the SnRK2 proteins found in plants have yet to be elucidated. Arabidopsis contains at least 12 SnRK2 proteins that have significant similarity (49% amino acid identity and 60% amino acid similarity over most of the protein) with SAC3.…”
Section: Regulation Of the Cys Biosynthetic Pathwaymentioning
confidence: 99%
“…nase, SPK4 (Yoon et al, 1997), was used as a marker for soluble proteins. Also, a polyclonal anti-PIPl antibody (a gift of Dr. Schaffner, Ludwig-Maximilians-Universitat) raised against a plasma membrane small-channel protein, PIP1 (Kammerloher et al, 1994), was used as a marker for membrane proteins.…”
Section: Adl1 Is Associated With Membranesmentioning
confidence: 99%
“…Expression of the genes encoding soybean (Glycine max) protein kinases SPK-3 and SPK-4, both members of this subfamily, are induced by dehydration and high salinity (Yoon et al, 1997). Two other soybean protein kinases, i.e.…”
mentioning
confidence: 99%